Implementasi Metode Multi Attribute Utility Theory dalam Menentukan Pengahargaan kepada Karyawan Terbaik - Eko Syaputra, Aldo; Budiarti Rahayu Putri, Perra (Universitas Putra Indonesia YPTK Padang, 2023)
Employees are very important human resources (HR) in business entities / companies. The development of a business entity is driven by employees who have high quality and loyalty. The purpose of this research is to determine the best employees who are entitled to receive awards / rewards from sanjai stores. To support the purpose of this research, the MAUT method is used because it has the ability to select alternatives efficiently and effectively because the time required for calculation is shorter based on predetermined criteria. Furthermore, the ranking process is carried out to determine which employees are entitled to an award. The data used are several criteria that have been determined by the store in determining the best employees and are entitled to receive awards, among these criteria include length of work, attendance, job knowledge, cooperation, responsibility, honesty, and age.The calculation results obtained using the MAUT method recommend the best employee AL03, with the highest score of 0.669. So that this research can be an objective material for the sanjai shop in determining the best employees.